2016
DOI: 10.1152/ajprenal.00423.2015
|View full text |Cite
|
Sign up to set email alerts
|

ROMK inhibitor actions in the nephron probed with diuretics

Abstract: Kharade SV, Flores D, Lindsley CW, Satlin LM, Denton JS. ROMK inhibitor actions in the nephron probed with diuretics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
2
10
0
1
Order By: Relevance
“…In addition, the inhibition of ROMK at the CCD, where it participates in potassium secretion, may ameliorate the hypokalemia resulting from the use of loop and thiazide diuretics. These assumptions are consistent with recent data showing that the major diuretic target site of compound A is the TALH, and that the compound prevents the kaliuretic response caused by either bumetanide or HCTZ as a consequence of its inhibitory actions at both TALH and CCD (Kharade et al, 2015). The results presented in this study with MK-7145 also support these expectations of a ROMK inhibitor, and further illustrate constant diuretic and blood pressure effects in SHRs, without evidence for the development of diuretic resistance during the course of the experiments.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the inhibition of ROMK at the CCD, where it participates in potassium secretion, may ameliorate the hypokalemia resulting from the use of loop and thiazide diuretics. These assumptions are consistent with recent data showing that the major diuretic target site of compound A is the TALH, and that the compound prevents the kaliuretic response caused by either bumetanide or HCTZ as a consequence of its inhibitory actions at both TALH and CCD (Kharade et al, 2015). The results presented in this study with MK-7145 also support these expectations of a ROMK inhibitor, and further illustrate constant diuretic and blood pressure effects in SHRs, without evidence for the development of diuretic resistance during the course of the experiments.…”
Section: Discussionsupporting
confidence: 92%
“…These responses are different from those induced by inhibitors of the renal outer medullary K 1 channel [ROMK (or Kir1.1)], another emerging diuretic target in the Kir channel family (Denton et al, 2013). We and others have shown that ROMK inhibition evokes diuresis and natriuresis without causing K 1 wasting (Garcia et al, 2014;Kharade et al, 2016;Zhou et al, 2017). The K 1 -sparing effect appears to result predominantly from the inhibition of K 1 secretion in the TAL with a relatively minor effect on distal K 1 secretion (Kharade et al, 2016).…”
Section: Discussionmentioning
confidence: 82%
“…All studies involving animals were approved by Institutional Animal Care and Use Committee. Metabolic cage studies were performed as described previously (Kharade et al, 2016). Briefly, male Sprague-Dawley rats (250-300 g) were allowed to acclimatize to single housing in metabolic cages for 2 hours before an experiment.…”
Section: Metabolic Cage Studiesmentioning
confidence: 99%
“…Specifically, ROMK variant 2 (ROMK2) contains an N-terminal mitochondrial localization sequence, and although its endogenous expression could only be detected by reverse-transcriptase polymerase chain reaction (RT-PCR), overexpression of recombinant ROMK2 fused to an epitope tag allowed immunodetection of its co-localization with mitochondrial markers. Recently, specific ROMK2 activators have been reported [168–170], but it is yet to be determined if these molecules can elicit protection against IR injury or activate a mitochondrial K + flux. In addition, although a whole-body ROMK knockout exists [171,172], renal insufficiency and hypertension render this model unsuitable for cardiovascular studies such as IR injury, and as of the submission of the present study, a cardiac-specific ROMK knockout mouse has not been reported.…”
Section: Mitochondrial Katp Channel: Composition Pharmacology Regulmentioning
confidence: 99%